Democracy And Social Welfare - DE880 - 202102 - De Urioste Samanamud, Roberto Ricardo (2021)
In this course we will examine some main contemporary philosophical and social scientific thinking concerning the moral foundations of democracy and some of its principal institutions. We will examine some of the main philosophical arguments about the value of democracy. What do we mean by ¿democracy¿? Is the value of democracy grounded in the results it produces or is there also some intrinsic fairness to democracy that counts in its favor? We will ask about the moral foundations of majority rule, one-person one-vote, and the legitimate role of democratic decisions in the society overall and the appropriate limits to democratic authority. We will look at some of the main economic approaches to democracy and the challenges they pose to the some of the main views about the value of democracy. We will examine Arrow¿s impossibility results in social choice theory and attempt to determine what implications it might have for our valuation of democracy. We will consider economic contractarian approaches to the foundations of democracy and think about what the contractarian approach has to offer. We will examine Anthony Downs¿ arguments for the thesis that the economically rational citizen is likely to be quite ignorant of politics. And we will attempt to ascertain what implications there might be for the value of democracy. We will discuss some principal moral issues that arise for democratic societies such as whether and when democratic decisions ought to be limited morally speaking. And we will ask whether this ought to be by constitutional limitations and judicial review. Finally, we will look at the moral significance of the different ways money influences the democratic process. We will look at these with an eye to developing a careful philosophical understanding of the basis of democracy (or lack thereof) and by means of thinking about and constructing rigorous philosophical arguments about democracy.